Evaluasi Website Pusat Pengembangan Karir dari Perspektif User Experience - Adindha Karunia Ciptaning Pragowoaji; Irwan Iftadi; Rahmaniyah Dwi Astuti (Jurnal Rekayasa Sistem Industri, 2023)
With the launch of the career development center (CDC) website in the digital era, XYZ university in Indonesia takes the initiative to serve as a liaison between students and companies in need of new talent. The website is intended to distribute job market and career development information to students and graduates. However, no evaluation directly involving students and graduates was conducted during the development process. As a result, this study aims to assess the level of user experience to comprehend users' perceptions of the current CDC website. The User Experience Questionnaire (UEQ) is used in this study to assess students' and alumni's perceptions as one entity. In addition, semi-structured interviews are conducted to better understand users' pain points. From the measurement with UEQ, the website's attractiveness got a positive impression from users with 0,99 points. The pragmatic quality aspect also makes a positive impression. This aspect consists of three variables: perspicuity (1,21 points), efficiency (0,83 points), and dependability (1,12 points). In contrast, the stimulation (0,74 points) and novelty (-0,37 points) variables on the hedonic quality aspect leave the user with a neutral impression. Based on interviews, users believe that the job vacancy information available on the CDC website still needs to be improved in quantity and variety. Users also need help finding the novelty aspect in terms of website appearance. This study successfully incorporated UEQ into the evaluation stage of a university's career development center website, which had never been done in previous research.